WAYS TO IMPROVE THE RELIABILITY OF DIESEL LOCOMOTIVES BY IMPROVING THE DIESEL COOLING SYSTEM - U. I. Abdulatipov; U.U. Yolchiyev; A.A. Baxronov (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Abstract: In order to improve the reliability and efficiency of locomotives used in the Republic of Uzbekistan, this article presents methods for increasing the reliability and efficiency of cooling systems. In particular, the advantages and disadvantages of these methods were analyzed and the installation of a water filter in the locomotive cooling system was proposed as one of the optimal solutions.